Right of customers in their transaction if they are deceived (Khiyar al-Tadlis) as proposed by Islam - Awang Hamat, Mohd Afandi; Fadzil, Ammar (2013)
khiyar at-tadlis basically promotes the concept of justice and fairness, it also provided a practical solution for both parties that involve in any contractual agreement namely the right to revoke or continue with the contract, basically it is called as ‘haqq al-khiyar’. Therefore, this paper attempts to discuss in detail the right of al-khiyar in business transaction as proposed by Islam. Therefore, in Islamic Law, Based on the doctrine of al-khiyar, any party who is dissatisfied with his or her contractual agreement, having the right to reconsider his or her decision in buying or selling something either to continue with such contract or to revoke it. The act of al-tadlis could occur when the seller deliberately deceives or exploits a potential buyer by any means of trickery, either by word or deed, that consequently influences the ignorant buyer to enter into the sale and purchase agreement, which finally leads him or her to purchase something what he or she would not have purchased it otherwise. It is pertinent to note that all four Muslim schools of law, in principal reject the notion of al-tadlis or concealing the defect of the commodity in any business transaction from the knowledge of the buyer. hanafi jurists consider such act of hiding the defect as a forbidden act, Maliki jurists explicitly describe it as the act of tadlis. Whilst Shafi' and hanabali jurists label it as the act of ghishsh (cheating). This paper will discuss in details various issues in khiyar al-Tadlis according to Four Sunni Mazhab.